Pengaruh Influencer Marketing, Brand Awareness, Dan Brand Love Terhadap Keputusan Pembelian Produk Scarlett Pada Tiktok Shop. (Studi Kasus Mahasiswi Kecamatan Lowokwaru) - Pratiwi, Revita Widya; Rachma, N; Utama, Satria Putra (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to determine and analyze the effect of influencer marketing, brand awareness, and brand love on purchasing decisions for scarlett products at tiktok shop. The method used in this study was purposive sampling with a sample size of 98 respondents using the slovin formula in determining the sample. The population of this study were college students in Lowokwaru sub-district who used scarlett products. This research method uses quantitative methods. Data was collected throught questionnaires distributed to college students in Lowokwaru District. The data analysis technique in this study used SPSS using multiple linear regression tests. The results showed that Influencer Marketing, Brand Awareness, and Brand Love simultaneously have a positive and significant influence on purchasing decisions. Keywords: Purchase Decision, Influencer Marketing, Brand Awareness, Brand Love